Industry churning and the evolution of cities: evidence for Germany - Sebastian Findeisen; Jens Suedekum (Institute for the Study of Labor (IZA), 2007)
In this paper we show that the recent model by Duranton (AER, 2007) performs remarkably well in replicating the city size distribution of West Germany, much better than the simple rank-size rule known as Zipf's law. The main mechanism of this theoretical framework is the churning of industries across cities. Little is known so far about the determinants of local industry turnover, however. We present an empirical analysis of the excess churning index for West German cities, which describes the strength of intra-city industry reallocations that has occurred over time. We find that human capital is a key driver of growth and local industrial change, but only among successful cities. Industrial change within unsuccessful cities is strongly driven by the disappearance of old-fashioned and declining industries such as agriculture or mining. On a more general level, our results suggest that the recent model by Duranton is a powerful description of the urban growth process. Still there are some aspects that are not captured by that model, which are at the core of other theories of urban growth.
Keywords: O18; 330; Industry turnover; urban growth; structural change; churning; city size distribution; Zipf's law; Stadtentwicklung; Industrieverlagerung; Städtische Bodennutzung; Stadtgröße; Stadtgeographie; Deutschland